2021
DOI: 10.1061/(asce)co.1943-7862.0002104
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Engineering Estimates for Best Value Design–Build Highway Projects

Abstract: Traditional design-bid-build guidelines suggest that engineering estimates should be within +/-10% of the lowest contractor bid and recommend this value as a reference to identify anomalies in the bidding process. This guidance, however, neglects delivery approaches such as design-build.This research examines 305 design-build highway projects procured using best-value and identifies the underlying reasons for bid dispersion and cost estimates inaccuracies. This study found an average bid dispersion of 27%, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In US design-build best-value procurement, highway agencies consider non-cost factors (Choi et al 2020;Papajohn et al 2019) by including a wide variety of evaluation criteria. However, previous research has pointed out that the selection of design-builders is heavily skewed toward price (FMI 2018;Gaikwad 2019). The design-build utilization study by FMI (2018) determined that, despite using non-cost selection criteria, highway agencies make the majority of their selection based on price.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In US design-build best-value procurement, highway agencies consider non-cost factors (Choi et al 2020;Papajohn et al 2019) by including a wide variety of evaluation criteria. However, previous research has pointed out that the selection of design-builders is heavily skewed toward price (FMI 2018;Gaikwad 2019). The design-build utilization study by FMI (2018) determined that, despite using non-cost selection criteria, highway agencies make the majority of their selection based on price.…”
Section: Introductionmentioning
confidence: 99%
“…The design-build utilization study by FMI (2018) determined that, despite using non-cost selection criteria, highway agencies make the majority of their selection based on price. Further, reviews of the bidding results of 305 DB best-value highway projects in the US also reveals that 80% of the projects were awarded to the lowest bidder on a sample of projects from 15 states between 2005 and 2018 (Gaikwad 2019). Thus, although highway agencies consider non-cost criteria in the evaluation, most of these criteria are not influential in the decision.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that after two decades of using best-value procurement, 80% of the projects were awarded to the lowest bidder [9,10]. Based on these data, it might be argued that best-value procurement works as the low-bid procurement with a selection only based on cost.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The final score (FS) for each proposer is the result of the award algorithm formula in each case, as indicated by Eqs. (10) and (11).…”
Section: Weighted Criteria Two Components and Three Componentsmentioning
confidence: 99%
See 1 more Smart Citation